Inhibition of CaMKII in Mitochondria Preserves Endothelial Barrier Function After Irradiation - Roy, Stephen J. (Free Radic Biol Med, 2019)
Damage to the microvascular endothelium is an important part of normal tissue injury after radiation exposure and driven by the production of pro-oxidants. The Ca(2+)/calmodulin-dependent protein kinase II is present in the mitochondrial matrix (mitoCaMKII) where it regulates Ca(2+) uptake via the mitochondrial Ca(2+) uniporter (MCU) and pro-oxidant production. Here, we demonstrate that radiation exposure disrupts endothelial cell barrier integrity in vitro, but can be abrogated by inhibition of mitoCaMKII, MCU, or opening of the mitochondrial transition pore. Scavenging of mitochondrial pro-oxidants with mito-TEMPO before, but not after irradiation, protected barrier function. Furthermore, markers of apoptosis and mitochondrial pro-oxidant production were elevated at 24 h following irradiation and abolished by mitoCaMKII inhibition. Endothelial barrier dysfunction was detected as early as two hours after irradiation. Despite only mildly impaired mitochondrial respiration, the intracellular ATP levels were significantly reduced 4 h after irradiation and correlated with barrier function. MitoCaMKII inhibition improved intracellular ATP concentrations by increasing glycolysis. Finally, DNA double strand break repair and non-homologous end joining, two major drivers of ATP consumption after irradiation, were greatly increased but not significantly affected by mitoCaMKII inhibition. These findings support the hypothesis that mitoCaMKII activity is linked to mitochondrial pro-oxidant production, reduced ATP production, and loss of endothelial barrier function following irradiation. The inhibition of mitoCaMKII is a promising approach to limiting radiation-induced endothelial injury.